GAMBLING CHARACTERISTICS PURSUANT TO CRIMINAL LAW RELATED TO BINOMO APPLICATION - Sadjijono, Prof. Dr. Sadjijono; Moersidin, Murry Darmoko; Prasetyo, Dr. Dossy Iskandar; Catalina, Jane (jfpublisher, 2024)
Binomo is an online trading platform that provides a wide selection of assets to trade (foreign currencies, gold, and stocks). The Binomo application shows a graphic display (chart) where the chart displays the price movement of an asset. The purpose of this study is to determine the characteristics of gambling in Indonesian criminal law and analyze the Binomo application in the perspective of gambling crime. This research is a type of normative research that describes in detail the social phenomena that are the subject matter in everyday life associated with using a statutory approach. The results of this study indicate that the characteristics of the Binomo application have fulfilled the elements of gambling in Article 27 Paragraph 2 of the Electronic Information and Transactions Law because of the element of intentionally making accessible Electronic Information and/or Electronic Documents that have gambling content. This is proven by the existence of the Binomo website which is categorized as an electronic document and contains gambling characteristics, namely guessing with a deposit as a bet and can be accessed by the public easily.